2019
DOI: 10.1016/s2215-0366(19)30180-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiple adverse outcomes following first discharge from inpatient psychiatric care: a national cohort study

Abstract: Summary Background Discharged psychiatric inpatients are at elevated risk of serious adverse outcomes, but no previous study has comprehensively examined an array of multiple risks in a single cohort. Methods We used data from the Danish Civil Registration System to delineate a cohort of all individuals born in Denmark in 1967–2000, who were alive and residing in Denmark on their 15th birthday, and who had been discharged from their first inpatient psychiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(102 citation statements)
references
References 30 publications
6
94
1
1
Order By: Relevance
“…A case-management type of remote transitional follow-up could be provided for this high-risk population. The aim would be to accompany patients in their experience of a twofold reality: early hospital discharge and the experience of confinement at home (42)(43)(44)(45). Patients discharged from the hospital have not had the opportunity to anticipate confinement and may find themselves in situations of major stress and discomfort.…”
Section: Reorganization Of Psychiatric Institutions In the Healthcarementioning
confidence: 99%
“…A case-management type of remote transitional follow-up could be provided for this high-risk population. The aim would be to accompany patients in their experience of a twofold reality: early hospital discharge and the experience of confinement at home (42)(43)(44)(45). Patients discharged from the hospital have not had the opportunity to anticipate confinement and may find themselves in situations of major stress and discomfort.…”
Section: Reorganization Of Psychiatric Institutions In the Healthcarementioning
confidence: 99%
“…Un suivi de type case-management de transition à distance pourrait être prodigué pour cette population à haut risque. Il s'agira d'accompagner les patients dans leur expérience d'une double réalité : la sortie précoce de l'hôpital et l'expérience du confinement au domicile (42)(43)(44)(45). Les patients sortis de l'hôpital Ce travail d'éducation à la santé est non seulement une contribution utile en termes de santé publique, mais il est psychiquement rassurant pour les patients et leurs proches.…”
Section: Vulnérabilité De L'organisation Des Soins Psychiatriques à Lunclassified
“…Discharge from acute mental health services is often described as a dangerous, chaotic, and emotionally driven time-period for patients (1). This time period has long been associated with mortality, risk, and related adverse outcomes for patients (2)(3)(4)(5). In England, between 2006 and 2016, there were 2,220 suicides within 3 months of discharge from inpatient mental health care (2).…”
Section: Introductionmentioning
confidence: 99%
“…In England, between 2006 and 2016, there were 2,220 suicides within 3 months of discharge from inpatient mental health care (2). Discharged individuals are at much higher risk than the rest of the population for a range of fatal and nonfatal adverse outcomes (5). For example, a recent cohort study in Denmark found that within 10 years of their first discharge, 37.1% of males will have died, harmed themselves, committed a violent crime, or been hospitalized due to interpersonal violence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation